OPERATION AND DEFENSIVE ROLE OF ＂GIN TRAPS＂ IN A COCCINELLID PUPA (CYCLONEDA SANGUINEA) - Eisner, Thomas; Eisner, Maria (Psyche (Cambridge, Mass.), 1992)
The flipping behavior of C. sanguinea pupae is evidently defensive. Ants are deterred by the maneuver itself, as well as by its concomitant, the pinching action of the gin traps. Other insect predators (as well as parasitoids?) may be deterred as well, but ants are probably among the principal enemies of coccinellid pupae. While, as noted by Hinton (1955), gin traps are widely distributed in Coccinellidae, they are not universally present in pupae of the family. Pupae of the Mexican bean beetle (Epilachna varivestis), for example, lack the traps, but they possess an alternative defense in the form of a covering of glandular hairs. The secretion associated with these hairs contains an interesting novel compound, currently under investigation (A. Attygalle, C. Blankespoor, J. Meinwald, T. Eisner, unpublished). Gin traps have been the subject of little physiological work, except in Sphingidae, where much has been learned from studies of the neuronal control and development of control of the pupal gin trap reflex (see, for instance, Levine et al. 1986, Levine 1989, and Waldrop and Levine 1989). Coccinelid gin traps could doubtless also lend themselves to further study.